Dating Status and Sociability as Predictors of Academic Performance among University Students - Omolayo, Benjamin O.; Awe, Phebe B.; Akinyemi, Elizabeth O.; Balogun, Morakinyo O. (Archives of Business Research, 2018)
Overtime, academic performance has been an area of interest in research in terms of looking at factors that influences academic performance. However, this study investigated dating status and sociability as predictors of academic performance among undergraduate students. A cross-sectional study was conducted in selected 8 Departments from 4 Faculties at Federal University Oye-Ekiti, Nigeria. A total of 200 participants were involved in the study comprising of 124 male and 76 female. A validated semi-structured questionnaire was used to investigate dating status and sociability while academic performance was based on students’ CGPAs. The data were analysed using descriptive, chi-square, ANOVA and t-test for independent samples. Results showed that dating status has no significant influence on academic performance (F=0.721, df=199, p>.05) while sociability has a negative influence on academic performance (t=2.046, df=159, p<.05). Having reading/interacting friends have a significant relationship with academic performance (x2=16.930, p<.05). The study made an important contribution to the body of knowledge on dating status and sociability as predictors of academic performance